Dynamic changes of serum matrix metalloproteinases and tissue inhibitors in Kawasaki disease: implications for coronary artery lesions persistence - Yaqi Li; Yao Lin; Chen Shen; Jing Zhang; Hui Wang; Qin Zhang; Lin Shi (Italian Journal of Pediatrics)
Abstract Background The mechanism of coronary artery lesions (CALs) persistence in Kawasaki disease (KD) remains unclear. The study aimed to investigate the serum dynamic changes of matrix metalloproteinases (MPPs) and tissue inhibitors (TIMPs) in children with CALs caused by KD, and explore their correlation with short-term CAL outcomes. Methods This is a nested case-control study. A total of 114 KD children with CALs completed the 3-month follow-up in discovery set and validation set. Children with CALs persisted after 3 months were enrolled as the CALs persistence group. The CALs regression group consisted of children with CALs regressed who were matched with each CALs persisted case by gender and age at a ratio of 2:1. In the discovery set, serum MMPs and TIMPs were measured using a Quantibody® Human MMP Array in febrile (before IVIG infusion) and defervescence phase (afebrile 48–72 h after initial treatment). Differential proteins between groups were identified by absolute logFC > 0.263 and adjust P value < 0.05. The findings were then validated in the independent validation set. Results There were 8 (13.3%) KD children with CALs that persisted for 3 months in the discovery set, including 4 boys and 4 girls, with a median age of 3.00 years. In the febrile phase, there were no differences in MMPs and TIMPs between CALs persistence group and CALs regression group (P>0.05). After treatment, MMP-8 and MMP-9 decreased in both groups, while TIMP-1 was lower in CALs persistence group (P<0.05). Further validation study showed the same changes. Conclusions MMPs and TIMPs have dynamic changes in children with CALs caused by KD. A low level of TIMP-1 after treatment may be related to CALs persistence, offering novel insights into the underlying mechanism.